2007
DOI: 10.1159/000109354
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Psychopathological Profile of Patients with Vulvodynia: An Observational and Descriptive Study

Abstract: Background: Vulvodynia is a fairly common dermatological symptom that often interferes with the personal, social and working activities of affected women and results in a significant loss of their quality of life. It is a persistent and tedious clinical disorder which is often resistant to conventional treatments. Objectives: The aim of this study is to evaluate the main clinical signs, associated psychopathological disorders and outcome after antidepressant treatment of patients with vulvodynia. Methods: Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…Pharmacological or behavioral treatment can also have a substantial impact on reduction of symptoms, [16][17][18] with a recent study demonstrating complete symptom resolution in Ͼ40% of patients treated with combination antidepressent therapy for 6 months. 19 Even if symptoms had resolved, however, original cases still should have answered "yes" to the vulvodynia screening question, as it queried for lifetime history of symptoms. Alternately, these cases may have denied symptoms because of embarrassment or discomfort as a result of the possibility of being overheard by others in close proximity during the time of the survey.…”
Section: Incidence Of Vulvodynia Symptoms In Us Women 1289mentioning
confidence: 99%
“…Pharmacological or behavioral treatment can also have a substantial impact on reduction of symptoms, [16][17][18] with a recent study demonstrating complete symptom resolution in Ͼ40% of patients treated with combination antidepressent therapy for 6 months. 19 Even if symptoms had resolved, however, original cases still should have answered "yes" to the vulvodynia screening question, as it queried for lifetime history of symptoms. Alternately, these cases may have denied symptoms because of embarrassment or discomfort as a result of the possibility of being overheard by others in close proximity during the time of the survey.…”
Section: Incidence Of Vulvodynia Symptoms In Us Women 1289mentioning
confidence: 99%
“…[28][29][30][31] We found that very few women were being treated for their vulvar pain, with the most likely treatment being topical estrogen -progesterone. Treatments were not associated with remission or relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Podstawą rozpoznania jest szczegółowo zebrany wywiad, brak odchyleń w badaniu przedmiotowym oraz badaniach laboratoryjnych. Choroba znacząco obniża jakość życia, utrudniając codzienne funkcjonowanie w sferze seksualnej oraz psychospołecznej, i nierzadko współwystępuje z depresją, zaburzeniami obsesyjno-kompulsywnymi oraz zaburzeniami lęko-wymi [8,9]. Dotąd nie opublikowano jednoznacznych wytycznych dotyczących postępowania terapeutycznego, popartych badaniami z randomizacją.…”
Section: Wstępunclassified
“…The disease has been shown to significantly decrease the quality of life in affected patients, and have a severe adverse impact on their psychosocial and sexual functioning. It is not uncommon for women with vulvodynia to also suffer from depression, obsessive-compulsive and anxiety disorders [8,9]. There are, as yet, no definitive published guidelines for the therapeutic management of the condition, supported by randomized trials.…”
Section: Introductionmentioning
confidence: 99%